Sero-prevalence and risk factors associated with occurrence of anti-Brucella antibodies among slaughterhouse workers in Uganda - Bugeza, James; Roesel, Kristina; Mugizi, Denis; Alinaitwe, Lordrick; Kivali, Velma; Kankya, C.; Moriyon, I.; Cook, Elizabeth A.J. (2024)
Introduction Brucellosis is a febrile zoonosis occurring among high-risk groups such as livestock keepers and abattoir workers and is a public health priority in Uganda. The technical complexities of bacteriological and molecular methods make serological approaches the cornerstone of diagnosis of human brucellosis in resource limited settings. Therefore, proper application and interpretation of serological tests is central to achieve a correct diagnosis.